Review of Nanocomposites as Anti-Corrosion Coatings on Steel Military Vehicles - Adisty Sidauruk; Sovian Aritonang (International journal of technology and education research, 2026)
Corrosion is a serious problem that causes economic and environmental losses in various industrial sectors, including the military, with global costs exceeding 2.5 trillion annually. Corrosion can reduce the lifespan and performance of military equipment, increase maintenance costs, and affect operational readiness. One solution to protect metals is the use of polymer-based coatings. Nanocomposites are synthesized through a mixing process between an epoxy matrix and uniformly dispersed nanoparticles. Recent research has developed epoxy nanocomposites with nanoparticles such as TiO₂, ZnO, and SiO₂ to enhance mechanical properties and corrosion resistance. Results from several related studies show significant improvements in corrosion resistance, with certain composites such as PANi/TiO₂ and PDMASTiO₂ demonstrating good efficiency and resistance to extreme environments, which could potentially extend the lifespan of military equipment and reduce maintenance costs.